Wahre und falsche Heiligkeit. Mystik, Macht und Geschlechterrollen im Katholizismus des 19. Jahrhunderts - Wolf, Hubert (Schriften des Historischen Kollegs, 2013)
The charges brought in an Inquisition case that revealed scandalous conditions in the Roman Catholic cloister of Sant Ambrogio between 1859 and 1862 included pretense of holiness and attempted murder. Possible motivations for the crimes included power struggles, jealousy, and a cover-up of sexual liaisons. Historians, theologians, religious scholars, and a psychiatrist shed a multifaceted light on the case.